Coletânea de analogias utilizadas no ensino de Física em turmas de ensino médio - Hartje, Raphael Guilherme Alves (2017)
Analogies are a resource widely found in many everyday situations. Its use is observed from an informal conversation between two people even in informative science texts. The analogies have been the object of interest and study of several researchers since the 1980s, both nationally and internationally. According to an Ausubelian view, analogies represent a potentially useful didactic resource, because they work with students' preexisting knowledge, thus helping in the formation/evolution of their cognitive structure, as well as making abstract concepts more intelligible. Its use also makes scientific language clearer, which for many is hard, dry and cold. Looking at analogies from Gardner's research, its application stimulates the development of the subject's multiple intelligences, since whatever analogy is used, according to Gardner, the subject will be using one or more of his Intelligences to try to understand it. This work will also contemplate minutiae about analogue language, such as its emergence, its functions, the spontaneity of analogical thinking in the human mind, the various situations in which we observe its manifestation, as well as its vulnerabilities and, finally, a comparison between its use and the Of other teaching methods. And finally, as a consequence of this study and based on the author's concerns about the observed difficulties of the students in the discipline of Physics, it appears, at the end of this work, a collection of analogies created by the author as a complementary teaching proposal. It is believed that in this way, learning is more enjoyable, effective and meaningful. Key-words: Analogies. Teaching Physics. Teaching methods.